IMPLEMENTATION OF TIME SERIES FORECASTING ALGORITHM IN THE 'MUSLIMAH CALENDAR' APPLICATION - Suci, Amalia Putri Permata; Asnawi, Muhamad Fuat; Hasanah, Nur (Nacreva Publisher, 2024)
Menstruation is blood that comes out of the farji (genitals) of a woman who is nine years old. In the book Risalah Haidl, it is explained that in several situations a Muslim woman who experiences menstruation is obliged to change her prayer. This Muslimah calendar aims to make it easier for users to predict the arrival of menstruation and record the prayer obligations incurred by a Muslimah. The algorithm implemented is the Time Series Forecasting Algorithm with Data Driven Prediction Exponential Smoothing Method, the sistem development method is waterfall, and the sistem design uses UML (Unified Modeling Language). This application uses the Flutter framework. The result of this research is an application that can estimate the start date of the menstrual period, the start date of the holy period and reminders of prayers that have not been done.